Liquid‐Amplified Electrostatically Driven Octopus Sucker‐Inspired Suction Cup - Yu Sun; Lingjun Tang; Ling Wang; Qingkai Guo; Yuxin Lv; Laihao Yang (Advanced Intelligent Systems)
Adhesion and detachment technologies play a crucial role in various fields, including industrial robot handling, transfer printing, medical applications, and crawling robot locomotion. Traditional pneumatic suction cups rely on bulky and noisy vacuum sources and need for preloading while electrostatic adhesion‐detachment devices generally cannot provide enough adhesion force. To address these shortcomings, a liquid‐amplified electrostatically driven suction cup is proposed inspired by octopus's sucker, including a negative pressure chamber with a wrinkle‐like membrane and a sealing ring. The negative pressure chamber generates the active adhesion force enhanced by the wrinkle‐like membrane, increasing the adhesion strength tenfold compared to pure electrostatic adhesion. The suction cup proposed herein has a remarkable capacity to generate an adhesion force of 56.4 times its weight, without preloading. Additionally, it can adapt to different materials, not only the dry but also the oil‐contaminated ones. This presented liquid‐amplified electrostatically driven suction cup can offer enhanced adhesion performance for applications in challenging environments.